Importance and Objectives of Marriage in Islam: An Analysis of Pakistani Nikah Namah in the Light of the Provisions of the Qur n and the Sunnah (Journal of Asian Development Studies, 2013)
This article presents a critical study of the provisions of Pakistani Nikāh Nāmah in the light of the teachings of the Qur’an and the Sunnah. It explores that lack of female education and existing cultural and male dominant phenomena forced the female of Pakistan to sacrifice her fundamental and Shar’i rights being a daughter, sister and most critically as a wife. Contrary to the provisions of the Qur’an and the Sunnah which empowered women and mostly have been legalized by way of legislation, Pakistani woman is still unaware regarding her marital rights and thus unable to utilize them. Moreover, biased interpretation of the Qur’ānic verses and the prophetic Sunnah regarding marital status and rights of the women have forced most of the women to prefer to suffer in silence rather than raising their voice against any kind of domestic or social violence. In this context, this article first analysis concept of marriage and its objectives in the light of Sharī‘ah Provisions and then evaluates provisions of Pakistani Nikāh Nāmah from the Perspective of the Qur’ān and the Sunnah. At the end some recommendations have been given to reform existing Nikāh Nāmah to secure the matrimonial rights of Pakistani female.